A White Race Blindness?: Abstract Universalism and the Unspeakable Making of Race. Issue 2 (1st June 2021) - Mazouz, Sarah
Abstract: Drawing on observations and on interviews conducted in a préfecture and in a municipalité of the Paris periphery, this article analyzes how republican universalism operates as a "particularizing" tool that enacts Whiteness. Starting from the paradoxical situation in which White state officials are reluctant to engage with the notion of racial discrimination when they are keen to ascribe racial categories to people of color, I argue that race blindness is in fact a form of White blindness to racialization. People of color who subscribe to the ideology of colorblindness tend to adopt a position whereby their loyalty toward the requirement of race blindness is supposed to protect them from suspicions raised by the racialized identity they are assigned to. But in practice, this stance internalizes the way they are viewed by Whites. The article concludes by discussing the link between White race blindness and the failure of republican policies against racial discrimination.